Geometric, Pavement, and Drainage Design of the Cibogo KM 9 Road Segment, Subang (±2 km) - Faqih, Muhammad; Mulyono, Sindy Budi; Permana, Rio; Sudrajat, Kukuh Mahi; Isradi, Muhammad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Road infrastructure development is crucial for mobility and the economy; design must satisfy geometric, structural, and drainage aspects. The research method used was a direct survey in the field to obtain primary data in the form of horizontal curve data, vertical slope, and other existing road geometric conditions. In addition, secondary data was obtained through literature studies and relevant supporting technical documents. This study analyzes the geometry of the Cibogo KM 9 road segment, ±2 km, in Padaasih Village, Subang. Referring to PDGJ 2021 and PKJI 2023; using 2025 LHR data, traffic growth of 8% (left direction) / 7.5% (right direction), a subgrade CBR of 5.5%, a design speed (Vr) of 70 km/h, and rainfall of 1,400–1,800 mm/year. The alignment produces 5 Spiral–Spiral curves with R = 250 m, the overlapping control is OK, and the cross-section type is 2/2 TT (two-lane, two-way, undivided). Drainage channel capacity from STA 0+000 – 2+024.63 using a 100 × 100 × 120 cm channel type (precast concrete), at 100-meter intervals, results in Q < Qsal. The design meets geometric criteria and base/drainage channel capacity requirements. These findings are expected to form the basis for recommendations for road improvements in the future.